A positioning kit for visually-impaired smartphone owners.
If you have ever had to rely on web mapping services to walk around a city, you probably noticed how positioning often lacks the precision required to do the job. Navocap, a French SME specialising in electronics, has developed a n app/positioning unit combo that should be of particular help to those suffering the most from this unreliability.